Concurrent Use of Biphasic Cuirass Ventilation and Low-intensity Noninvasive Positive Pressure Ventilation. Issue 1 (January 2020) - Tada, Mitsuhiro; Kadowaki, Toru; Tsubouchi, Yusuke; Nishikawa, Emiko; Iwamoto, Shinichi; Kobayashi, Kanako; Kimura, Masahiro; Ikeda, Toshikazu; Yano, Shuichi
Abstract : Noninvasive positive pressure ventilation (NPPV) is widely used for ventilatory support, but is not effective in some conditions, such as pneumothorax. Biphasic cuirass ventilation (BCV) is a form of negative pressure ventilation that uses an external cuirass-style ventilator to support both inspiration and expiration at various cycle rates and pressures. BCV theoretically provides ventilation in a more natural manner than positive pressure ventilation and lowers the risk of barotrauma by preventing an increase in airway pressure. The concurrent use of BCV and NPPV may increase tidal volume and decrease the PaCO2 level to a greater extent than NPPV alone without increasing airway pressure. Herein, we report on 2 patients with pneumothorax and insufficient NPPV in whom the concurrent use of BCV and low-intensity NPPV provided successful ventilatory support.